Changes in the surface hydrophobicity degree of a MCM-41 used as iron support: a pathway to improve the activity and the oleins production in the Fischer–Tropsch synthesis - Fellenz, Nicolás Antonio (2016)
The effect of surface hydrophobicity degree of MCM-41 support on activity and selectivity in Fischer?Tropsch synthesis has been studied. The Fe/MCM-41 catalyst was prepared by impregnation of the mesoporous support with iron. A portion of this product was silylated with hexamethyldisilazane. The samples were characterized by atomic absorption spectroscopy, X ray diffraction at low angles, N2 adsorption at 77 K, Fourier transform infrared spectroscopy and Mössbauer spectroscopy at 25 and 298 K in controlled atmosphere. Catalytic tests were performed simulating industrial operating conditions and showed that the silylated system presents higher activity, lower selectivity toward methane and higher olefin/paraffin ratio. The higher methane production and the lower amount of olefins observed for the non-silylated catalyst indicate that this system has a larger amount of hydrogen on its surface than the silylated one. A detailed discussion about the relationship among surface chemistry, stability, selectivity and the changes in iron species of the catalysts is presented.